Traditional Substitution Cipher – A Mathematical Overview and its Implementation - Nilesh Kajale, Mohan Reddy Palugulla, Rupali Bhakkad, (International Journal of Scientific Research and Management (IJSRM), 2015)
: Exchanging information over internet become crucial part of our day today life,which includes e-banking, online transactions, online shopping and exchange of official and personal information, as this type of information’s are sensitive , security of such critical information is becoming increasingly important. Information Security can be achieved with the help of cryptography. Cryptography is the study of mathematical techniques related to aspects of information security such as confidentiality, data integrity, entity authentication, and data origin authentication. Cryptography has been divided in two types, Symmetric key cryptosystem and asymmetric key cryptosystem. In order to work with the current era’s cryptosystem one should become familiars with the working of classical cryptosystem such as Shift cipher, affine cipher, substitution cipher and hill cipher techniques etc. This paper highlights the concept of classical symmetric key cryptosystem and its type and explains in detail elementary substitution cryptosystem (substitution Cipher) and polyalphabetic substitution cryptosystem (Hill Cipher) example with its mathematical overview and implementation in C++.